2015
DOI: 10.5296/ijafr.v5i1.7653
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Relation between CEO Remuneration and Banks' Size and performance?

Abstract: The goal of the study is to establish what kind of relationship, if any, exists between CEO remuneration and Banks size and performance. The study is extremely relevant, especially in the financial sector after the crisis of 2007-2008. Many critics have argued both as rhetoric as well as an empirical study that high executive pays have a negative impact on the sustainability and success of a firm. Studying the literature reveals plurality in positions. Since this is an extremely complex question, it is underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…Bruck, Liu, and Skovoroda (2008) concluded that the executive payment positively relates to the past and current firm financial performance. In contrast, Kutum (2015) found no significant relationship exists between CEO remuneration and bank performance in Canadian Banks except a weak positive relationship with return on assets (ROA).…”
Section: Literature Reviewmentioning
confidence: 83%
“…Bruck, Liu, and Skovoroda (2008) concluded that the executive payment positively relates to the past and current firm financial performance. In contrast, Kutum (2015) found no significant relationship exists between CEO remuneration and bank performance in Canadian Banks except a weak positive relationship with return on assets (ROA).…”
Section: Literature Reviewmentioning
confidence: 83%
“…The results revealed that there are significant relationships between corporate financial performance and CEO remuneration. Kutum (2015) reveals no significant relationship could be established between CEO remuneration and bank performance except a weak positive relationship with ROA. Buachoom (2015)'s study shows that compensation of executives in Thai firms corresponds to firms' performance, and compensation of executives leads to an improvement in subsequent performance of Thai listed firms.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 86%
“…Hasil yang serupa juga didapatkan oleh Balafas dan Florackis (2014) yang menggunakan perusahaan pada London Stock Exchange sebagai sampel penelitian serta variabel dependen dan independen yang digunakan adalah ROA dan remunerasi CEO. Menurut Balafas dan Florackis (2014), alasan atas hubungan negatif antara ROA dan remunerasi CEO yang dilakukannya adalah karena adanya faktor risiko seperti coskewness dan kurtosis, risiko unsystematic, dan tenor pada CEO baru dimana perusahaan berusaha untuk menetapkan standar remunerasi baru.Hal yang menarik selanjutnya terdapat pada penelitian yang dilakukan olehKutum (2015) yang memiliki hasil yang berbeda pada setiap indikator kinerja keuangan perusahaan yang diteliti yakni ROA, ROE, dan profit margin. Hasil penelitian menemukan adanya hubungan positif antara remunerasi CEO dan ROA namun remunerasi CEO tidak mempunyai hubungan dengan ROE dan profit margin.…”
unclassified
“…Hasil penelitian menemukan adanya hubungan positif antara remunerasi CEO dan ROA namun remunerasi CEO tidak mempunyai hubungan dengan ROE dan profit margin. Berbeda denganKutum (2015), penelitian yang dilakukan Demirer dan Yuan (2013) menemukan adanya perbedaan hasil yang disesuaikan dengan variabel dependen yang digunakan, remunerasi yang diukur dalam bentuk gaji memiliki hubungan negatif terhadap kinerja perusahaan sebaliknya hubungan negatif terhadap kinerja perusahaan didapatkan pada remunerasi dengan bentuk bonus dan non-ekuitas. Menurut Demirer dan Yuan (2013), hasil penelitian tersebut didasari dengan alasan bahwa sang pembuat keputusan (decision maker) lebih fokus pada pengambilan keputusan jangka pendek karena keputusan dalam jangka pendek dinilai akan memberikan dampak yang positif pada kinerja jangka panjang nantinya.…”
unclassified